Design of Computer Based Signal Generator - Abdelhadi Husein Aburawis; Imam Much Ibnu Subroto; Muhammad Qomaruddin (Universitas Islam Sultan Agung, 2016)
The project includes various types of signals alternative study and representation of a computer in digital format and out through the port as an outlet for the output of digital data to generate signals and electronic control circuit of the printer parallel LPTI prevailing used to generate signals. The aim of the research is to evaluate the usage of the computer including the advantage of its possibilities, capabilities in multiple signals processing, and control signal generation methods in many ways that are used to generate various signals at frequencies different capacities. The necessary software requires generating different types of signals, frequencies, and capacities. It is as well as the different software required for the purpose of controlling the electronic circuit. It has been relying on a programmatic method depends on the language of Visual Basic. In addition to the study of the physical system requirements, the analysis how to connect them with the computer and version control signals E-circle this study using speed of a transferring time for generator is Tc = 100nsec. The Speed of a computer which is used to treat ‘1000 MHz’, is got on the farthest frequency to get out from the circle is ‘2500 Hz’. It is used to different signals, sine, triangular or square in 30 samples. The sample numbers are tested. The result of this study shows that each of the sample number, input frequency, and sample time influence the results clearly. If the sample numbers increase, the accuracy of the waves increases. If the input frequency increases, the width of the wave losses. Keywords: Signal Generator, Computer, Visual Basic, Signals